Roles of specialized pro-resolving mediators and omega-3 polyunsaturated fatty acids in periodontal inflammation and impact on oral microbiota - Lee, Chun-Teh; Tribble, Gena D. (Frontiers in Oral Health, 2023)
Periodontitis is a chronic inflammatory disease induced by dysbiotic dental biofilms. Management of periodontitis is primarily anti-bacterial via mechanical removal of bacterial biofilm. The successful resolution requires wound healing and tissue regeneration, which are not always achieved with these traditional methods. The discovery of specialized pro-resolving mediators (SPMs), a class of lipid mediators that induce the resolution of inflammation and promote local tissue homeostasis, creates another option for the treatment of periodontitis and other diseases of chronic inflammation. In this mini-review, we discuss the host-modulatory effects of SPMs on periodontal tissues and changes in the taxonomic composition of the gut and oral microbiome in the presence of SPMs and SPM precursor lipids. Further research into the relationship between host SPM production and microbiome-SPM modification has the potential to unveil new diagnostic markers of inflammation and wound healing. Expanding this field may drive the discovery of microbial-derived bioactive therapeutics to modulate immune responses.